Development of Learning Media Based on Virtual Laboratory on Straight Motion Kinematics Materials - Pratiwi, Maharani Rizky; Purwaningsih, Sri; Lestari, Neneng (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
This study aims to determine the feasibility of laboratory virtual mediaon straight motion kinematics using modelsproblem based learning as well as knowing how students perceive when using the productthat have been developed are reviewed based on the feasibility of the content, graphics, appearance and language.The method used in this study is a quantitative research methodobtained from the results of assessments by media expert validators, material expert validators, and the results of student perception questionnaires regarding the product being developedwith a sample of 28 students. The sampling technique used was purposive sampling. The instruments used were media validation questionnaires, materials, and perception questionnaires. The data analysis used is descriptive statistics, in which the average result obtained from the five assessment indicators is 79.76% which indicates that the media is suitable for use and is greeted very positively by students who use it.